THE EFFECT OF PERCEPTION ON USE E-MONEY FUNDS AS A TRANSACTION TOOL (STUDY ON FISIPOL UNIVERSITAS MALIKUSSALEH STUDENTS) - Miyana Zaifatih; Cut Sukmawati; Maisyura; Lisa Iryani; Riyahi Praza (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Technological advances in payment systems have shifted the role of cash as a means of payment to a more efficient and economical form of non-cash payment. One of the non-cash payment instruments that is currently developing is electronic money or commonly called e-money. Perception is a determining factor for students in using e-money products. The convenience and benefits offered by e-money products can have an impact on increasing their users because students tend to use or not use the application as long as they are sure whether the application will help them better. In addition to the benefits, there are security risks in using e-money which is still very vulnerable to fraud or other crimes. Therefore, this is a challenge for electronic money issuers to create an electronic money system that is safe from crime. This study aims to see how perception influences the use of DANA e-money as a transaction tool for FISIP Unimal students. This study uses descriptive quantitative research with non-probability sampling as a sampling technique, so that 96 research samples are obtained. Data analysis used in this study uses simple linear regression with the help of the SPSS 25.0 software program. The results of the study indicate that partially the perception variable has a positive and significant effect on the use of DANA e-money as a transaction tool. This is because users really consider the perception of benefits, perception of ease of use and perception of risk of DANA e-money to be used as a transaction tool. It can be seen from the R square value which shows that 40% can be explained by the perception variable, while the remaining 60% is explained by other variables that are not included or discussed in this research model. Based on the results of the frequency of respondents' answers, there are statements that are generally answered less agree or neutral, namely on the risk perception indicator. This is because respondents feel less confident in providing personal data and making large transactions to DANA e-money. The reason is that respondents consider the security of DANA e-money to be still fairly poor, so that cases of account hacking and loss of money often occur.